Hubungan Antara Keharmonisan Keluarga dengan Perilaku Agresif pada Siswa - Annisa; Putri, Aulia Safira (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Teenagers are a group that has the potential to act aggressively. Teenagers are in a transition period which causes a lot of conflict, frustration and pressure, so they are likely to easily act aggressively. One of the factors that causes aggressive behavior in adolescents is family disharmony. For this reason, it is necessary to create harmony in the family. Because a happy and harmonious family can be a good place to educate children to become individuals with good personalities. This approach uses a quantitative correlational research type with a survey method, namely collecting data using a list of statements and giving it to respondents to answer. Apart from that, researchers also used interview and observation methods, by interviewing students who experienced aggressive behavior and directly observing the students’ behavior. Then the researcher examined the overall results of the questionnaire, interviews and observations, then the researcher was able to find conclusions regarding the factors that influence family harmony and aggressive behavior in students